Immune mechanisms targeting malaria transmission: opportunities for vaccine development - Geetha P. Bansal; Nirbhay Kumar (Taylor & Francis Group, 2024)
Introduction Malaria continues to remain a major global health problem with nearly a quarter of a billion clinical cases and more than 600,000 deaths in 2022. There has been significant progress toward vaccine development, however, poor efficacy of approved vaccines requiring multiple immunizing doses emphasizes the need for continued efforts toward improved vaccines. Progress to date, nonetheless, has provided impetus for malaria elimination.Areas covered In this review we will focus on diverse immune mechanisms targeting gametocytes in the human host and gametocyte-mediated malaria transmission via the mosquito vector.Expert opinion To march toward the goal of malaria elimination it will be critical to target the process of malaria transmission by mosquitoes, mediated exclusively by the sexual stages, i.e. male, and female gametocytes, ingested from infected vertebrate host. Studies over several decades have established antigens in the parasite sexual stages developing in the mosquito midgut as attractive targets for the development of transmission blocking vaccines (TBVs). Immune clearance of gametocytes in the vertebrate host can synergize with TBVs and directly aid in maintaining effective transmission reducing immune potential.